NLRP1 L155H Polymorphism is a Risk Factor for Preeclampsia Development. (29th December 2014) - Pontillo, Alessandra; Reis, Edione C.; Bricher, Pamela N.; Vianna, Priscila; Diniz, Solange; Fernandes, Karla S.; Chies, Jose A.; Sandrim, Valeria
<x xml:space="preserve">Abstract</x> Problem Augmented levels of IL‐1ß have been pointed out as an important pathogenic factor for preeclampsia development. Inflammasome is the cytoplasmic complex responsible for pro‐IL1ß cleavage and IL‐1ß secretion. Aim of the study was to evaluate the association between polymorphisms in inflammasome' genes and preeclampsia. Method of study Selected polymorphisms in inflammasome genes (NLRP1, NLRP3, CARD8, and IL1B) were analyzed in 286 Brazilian women with and 309 without preeclampsia. Results and Conlclusions The NLRP1 variant rs12150220 (L155H) was associated with the development of preeclampsia (OR = 1.58), suggesting a role of this inflammasome receptor in the pathogenesis of this multifactorial disorder.